Insulin resistance and non-alcoholic fatty liver disease: a review of the pathophysiology and the potential targets for drug actions - Taoreed Adegoke Azeez; Morenike Osundina (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Insulin resistance refers to the reduced physiological effects of insulin on various tissues. Insulin resistance has been implicated in the pathophysiology of non-alcoholic fatty liver disease (NAFLD), which is a spectrum of diseases ranging from hepatic steatosis on one end to steatohepatitis, liver cirrhosis and hepatocellular carcinoma on the other end. In most parts of the developed world, it is now the most commoncause of chronic liver disease and the most commonindication for liver transplantation. A similar findingis emerging in the developing world due to the rising prevalence of obesity and widespread adoption of Western lifestyles. Despite these epidemiological data, there are no universally approved medications for the treatment of NAFLD. The pathophysiological mechanisms of NAFLD essentially include adipose tissue insulin resistance, hepatic insulin resistance, inflammation and fibrosis. At the subcellular level, mitochondrial dysfunction, oxidative changes and endoplasmic reticulum dysfunction have been documented. Several drugs have been tested in vitro and in animal studies to target these pathophysiological mechanisms. Some are presently going through clinical trials, while others have already gone through clinical trials with variable results. Other potential target sites of drug development for the treatment of NAFLD are based on the complex pathophysiology of the disease. Insulin resistance plays an important role in the development of NAFLD. There are potential targets in the pathophysiology of NAFLD that can be explored in the development of medications for the disease.